Dynamics of Religiosity Among Russians and Some Methodological Problems of Its Study: (The Religious Consciousness and Behavior of Orthodox Christians and Muslims). Issue 1 (2nd January 2019) - Sinelina, Iu.Iu.
Abstract : Research on the dynamics of Russians' religiosity shows that there has been a relatively stable or slightly increasing level of participation in religious activities, but also that identifying oneself as Christian Orthodox is more a cultural than a religious phenomenon.